Modeling IoT Smart Home Network - U. A. Vishnyakou; Yu. Chuyue (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The purpose of the article is to present the process of modeling the IoT smart home (SH) network, which combines both user needs and efficiency requirements. The use of Alibaba cloud platform, which reduces complexity and development time, reduces costs, was justified in the project of building the IoT SH network. The structure of this platform is given, its main components are considered and an algorithm for its configuration is given. MQTT is used as an access protocol in the IoT SH network to achieve fast and reliable data transmission. Open source code, reliability, simplicity and other characteristics justify the choice of this data transfer protocol. Modeling of the network IoT SH is based on the knowledge gained in the process of practical implementation. First, the online problems of the system are tested, after the system is able to work after modification and debugging of programs, a street lamp is used as an example to create an instance of an IoT SH network on a cloud platform. The process of creating an example of an IoT SH network is described in detail in steps, in which data from a street lamp is transmitted to a cloud platform, processed there, and then displayed on a mobile device. A mobile phone was used to implement two-way interaction, simulate the sensor of the IoT SH network and display the results. The algorithms for configuring the platform, modeling the sensor and creating an object model of the device of the IoT SH network are given. For some modern control systems, this system is compatible and suitable for a larger number of cases, which contributes to the development of intelligent control in the IoT network.